PERANCANGAN AVIAN EDUCATION CENTER DI KOTA TANGERANG DENGAN PENDEKATAN ARSITEKTUR BIOFILIK - Princesca, Georgia; Buwono, Hanugrah Adhi; Asharhani, Imaniar Sofia (RUSTIC, 2024)
Indonesia is a country rich in fauna, described as a country with high levels of variety and endemism. Among these fauna, 1826 area birds and of those 1598 species, 528 birds are endemic to the country. As impressive as the variety of these birds is, it is also notable that 179 of these species are endangered, 31 already listed as critically endangered. Many of these species are endangered due to destruction of their natural habitats, poaching as well as the illegal trade of these birds. Overall, this is due to the ignorance of the people as well as the lack of education available to the general public regarding the importance of conserving these animals. This highlights how vital educating the community, especially the younger generation, of how important conserving these birds are to the entire ecosystem. Having a source of information that is not just accessible but also intriguing to the general public will impact animal conservation in its entirety. It is also important to design a space that can help people connect with not just the animal, but nature in general as to teach them to appreciate nature. Therefore, designing a space that is accessible to the general public, offers information in an educative, immersive and interactive manner and can help create a connection to nature is important to the goal of animal conservation.